2005
DOI: 10.1159/000086370
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Injuries following Falls by Hospital In-Patients

Abstract: Background: Falls are one of the most frequent episodes on the hospital wards. Objective: To identify orthopaedic injuries sustained by in-patients falling on the hospital wards and to find out what treatment these required along with the additional time and cost that this incurred. Methods: A retrospective analysis of 900 incident forms and case records was undertaken for a 3-year period. Fractures and other soft-tissue injuries sustained and time, place, and mode of injury were noted. Type of fractures susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 18 publications
3
35
1
1
Order By: Relevance
“…A study in the United Kingdom estimated costs of treating orthopaedic fall-related injuries that occurred in hospital over a 3-year period to be about £127000 (covering surgery and bed-costs only), with most patients with these injuries requiring between 1 and 5 weeks' additional stay in hospital. 31 Results similar to those of our study were obtained in another study in the US. 21 This previous study showed that hospital LOS was 12 days longer, and hospitalisation costs US$4233 higher for fallers than their non-falling counterparts when matched on age and gender and admission time frame.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study in the United Kingdom estimated costs of treating orthopaedic fall-related injuries that occurred in hospital over a 3-year period to be about £127000 (covering surgery and bed-costs only), with most patients with these injuries requiring between 1 and 5 weeks' additional stay in hospital. 31 Results similar to those of our study were obtained in another study in the US. 21 This previous study showed that hospital LOS was 12 days longer, and hospitalisation costs US$4233 higher for fallers than their non-falling counterparts when matched on age and gender and admission time frame.…”
Section: Discussionsupporting
confidence: 92%
“…An important difference in our study methodology was analysis within DRGs, which ensures similar groupings of admission causes. It should be noted that the results from our own study, and those of Bates and colleagues 21 and Nadkarni and colleagues 31 only incorporate costs associated with falls while an inpatient. Clearly, for some of these fallers the increased costs persist after discharge in terms of potential need for additional therapy and community support services, as well as indirect costs such as anxiety experienced by patients or caregivers, and these costs were not considered in these studies.…”
Section: Discussionmentioning
confidence: 86%
“…[2][3][4][5][6] Falls in hospital often result in injuries, increased lengths of stay, and greater costs to the health service. [6][7][8][9] Evidence on the best way to prevent falls in hospital is, however, limited. No single intervention, such as bed alarms or bracelets to identify patients at high risk of falls, has been proved effective in randomised trials.…”
Section: Introductionmentioning
confidence: 99%
“…As quedas de doentes internados não podem ser totalmente evitadas, ocorrendo apesar das medidas preventivas [17]. …”
Section: Introductionunclassified